In vivo and in vitro effect of capsicum annum proteinase inhibitors on helicoverpa armigera gut proteinases - Tamhane, V. A.; Chougule, Nanasaheb P.; Giri, Ashok P.; Dixit, A. R.; Sainani, Mohini N.; Gupta, Vidya S. (Biochimica Et Biophysica Acta-General Subjects, 2005)
Two proteinase inhibitors (PIs), CapA1 and CapA2, were purified from Capsicum annum Linn. Var. Phule Jyoti leaves and assessed for their in vitro and in vivo activity against Helicoverpa armigera gut proteinases (HGPs). Both the inhibitors exhibited molecular weights of about 12 kDa with inhibitory activity against bovine trypsin and chymotrypsin indicating presence of probable two-inhibitor repeats of PIN II family. CapA1 and CapA2 inhibited 60-80% HGP (azocaseinolytic) activity of fourth instar larvae feeding on various host plants while 45-65% inhibition of HGP activity of various instars (II to VI) larvae reared on artificial diet. The partial purification of HGP isoforms, their characterization with synthetic inhibitors and inhibition by C. annum PIs revealed that most of the trypsin-like activity (68-91%) of HGPs was sensitive to C. annum PIs while 39-85% chymotrypsin-like activity of HGPs was insensitive to these inhibitors. The feeding of C. annum leaf extracts and two purified PIs in various doses to H. armigera larvae for two successive generations through artificial diet demonstrated their potential in inhibiting larval growth and development, delay in pupation period and dramatic reduction in fecundity and fertility. This is the first report-demonstrating efficacy of C. annum PIs against insect gut proteinases as well as larval growth and development of H. armigera. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: Capsicum annum; gut proteinase; Helicoverpa armigera; insect resistance; Proteinase inhibitor

Podborer (Helicoverpa armigera Hubn.) does not show specific adaptations in gut proteinases to dietary Cicer arietinum Kunitz proteinase inhibitor - Srinivasan, A.; Chougule, Nanasaheb P.; Giri, Ashok P.; Gatehouse, J. A.; Gupta, Vidya S. (Journal of Insect Physiology, 2005)
We investigated the response of Helicoverpa armigera larvae towards ingestion of Cicer arietinum Kunitz proteinase inhibitor (CaKPI), which caused antagonistic effects on developing H. armigera larvae. CaKPI-degrading proteinases were not detectable in either control or sensitized larvae. There were negligible increases in total proteinase activity, as well as in trypsin-like and chymotrypsin-like activities of H. armigera gut proteinases (HGPs). Decrease in sensitivity of HGPs to inhibition by CaKPI was not observed when the inhibitor was fed Suggesting that the insect had not shown a specific adaptive response to dietary CaKPI. Semi-quantitative reverse transcriptase polymerase chain reaction (Q RT-PCR) analysis showed a general up-regulation of proteases in larvae that ingested CaKPI and a specific regulation of individual transcripts was not observed. CaKPI had maximum inhibitory activity against HGP derived from fourth instar larvae. CaKPI was equally potent in inhibition of HGPs derived from larvae fed on different host plants, as well as various proteinase inhibitors (Pis) to which larval adaptation was previously reported. The lack of larval response to CaKPI was attributable to the atypical active site sequence and inhibitory activity of CaKPI and/or to the pre-adaptation of H. armigera larvae due to the constant exposure to basal levels of CaKPI in chickpea seeds or a chickpea seed-based diet. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Cicer arietinum; Helicoverpa armigera; insect response; proteinase; Proteinase inhibitor